The festivals of Opet, the Valley, and the New Year : their socio-religious functions - Fukaya, Masashi (Archaeopress Egyptology, 2020)
This title compares the religious and social functions of the festivals of Opet, the Valley and the New Year, the first two of which were often regarded by the Egyptians as a pair; the New Year Festival stands out on account of its corpus of surviving material and importance. Until now, detailed study of the New Year Festival has only been carried out with reference to the Greco-Roman period; this study turns its attention to the New Kingdom. The book analyses the broad perspectives that encompass Egyptian religion and cult practices which provided the context not only for worship and prayer, but also for the formation of social identity and responsibility. The festivals are examined in the whole together with their settings in the religious and urban landscapes. The best example is New Kingdom Thebes where large temples and burial sites survive intact today with processional routes connecting some of them